Education and Polish School System in Belarus. Press Discourse Analysis of «Głos znad Niemna na uchodźstwie» in the Period 2014–2016 - Waldemar Zak (Pedagogical Discourse, 2019)
This article focuses on the press discourse analysis concerning education and Polish school system in Belarus which took place in the period 2014–2016 in «Głos znad Niemna na uchodźstwie» («A voice from the Neman River in Exile») weekly. The situation of the Polish minority in Belarus was always difficult because the politics of Belarusian authorities was focused on destruction of anything connected with Polish culture or possessing Polish roots: intelligentsia, school, theatres, press. The situation of Poles as Polish people living abroad in the contemporary Belarus seems to be complicated. On one hand, they form big percentage of the society in Belarus, but on the other hand, a significant part of them has a difficulty to preserve Polish identity. Consequently the role of Polish schools and organizations in education of children and teenagers has increased. Language acquisition begins in kindergartens during extra lessons or within Polish groups. The forms of language acquisition at school vary a lot. Most of the students learn Polish languages after-hours, some of them attends required Polish classes at school. Polish press in Belarus plays a vital role in the process of creation and development of national awareness. «Głos znad Niemna na uchodźstwie» weekly issued as the press organ of the Union of Poles in Belarus has been playing such a vital role for years. The discourse analysis has proved to be particularly helpful concerning some problematic issues of ethnic and national minorities. One should highlight the fact that the public discourse is used both for the formation and reinforcement of the national identity. We analyzed five selected papers concerning the education and Polish school system in Belarus in «Głos znad Niemna na uchodźstwie» weekly. We observed what topics concerning Polish education in Belarus are highlighted in the press, what the discourse construction is, types of used vocabulary and structures, what changes in readers’ behavior and mentality are obtained.